Psychological Problms of Pandemic Coronavirus Infections COVID-19 - Purtskhvanidze, Kristine; Shakarashvili , M.V (Caucasus Journal of Health Sciences and Public Health, 2020)
General Director of the World Health Organization has announced a new coronavirus COVID-19 as pandemic, which has been life threatening experience for humans. In all respects, millions of people are sitting on radical pens in their own lives - like economists and socialists, as well as doctors and psychologists. When deciding to fight against coronavirus, it is necessary to pay special attention to a psychological composition, such as perception, occupation, reaction and behavior in such situations. Danger of self-loathing and lively surroundings, restriction of self-esteem, change of mass modesty, prolonged contagious, self-isolation, limited contact, and uncertainty about uncertainty. Stress can provoke a sharp rise in chronic disease and a decrease in immunity, which increases the risk of infection. Furthermore, in the present time, the use of psychiatric and psychosocial well-being in the population has become a topical issue and requires a coordinated action by government and non-government organizations. In the event of an unforeseen occurrence, the consequences may be prevented or reversed by the use of a co-ordinating measure. To reduce the impact of psychological stress, with the aim of psychological assistance, it is necessary to carry out targeted explanatory work on the nature of the emergence and development of this emergency: that the current situation can pose a certain challenge to a person and that person, not resisting reality, must accept new circumstances, trust only official representatives of health care organizations, taking into account the new requirements, comply with the recommended preventive measures, rebuild about times of life and behavior and responsibly treat both : their health and the health of others. It should be noted that these psychological problems did not arise for everyone, but if it is impossible to cope with difficult feelings and emotions on their own, of course, you need to contact specialists - psychologists and psychotherapists.